Plower Cycle Enterprise : "Plower Cycle" / Mohamad Asraf Mohd Saif...[et.al] - Rostam, Zulkifli; Osman, Nur Fara'ain; Rashidi, Rahmah; Saba, Normarita (Faculty of Plantation and Agrotechnology, 2016)
PLOWER CYCLE Enterprise is a start-up manufacturing company that sells agro-technology product that is mainly manufactured to meet the demand of customer and competitively priced. The company is focused on high growth products driven by current technological trends, such as economy and appearance.